Insulin Regulates GABAA Receptor-Mediated Tonic Currents in the Prefrontal Cortex - Trujeque-Ramos, Saraí; Castillo-Rolón, Diego; Galarraga, Elvira; Tapia, Dagoberto; Arenas-López, Gabina; Mihailescu, Stefan; Hernández-López, Salvador (Frontiers in Neuroscience, 2018)
Recent studies, have shown that insulin increases extrasynaptic GABAA receptor-mediated currents in the hippocampus, causing alterations of neuronal excitability. The prefrontal cortex (PFC) is another brain area which is involved in cognition functions and expresses insulin receptors. Here, we used electrophysiological, molecular and immunocytochemical techniques to examine the effect of insulin on the extrasynaptic GABAA receptor-mediated tonic currents in brain slices. We found that insulin (20-500 nM) increases GABAA-mediated tonic currents. Our results suggest that insulin promotes the trafficking of extrasynaptic GABAA receptors from the cytoplasm to the cell membrane. Western blot analysis and immunocytochemistry showed that PFC extrasynaptic GABAA receptors contain α-5 and δ subunits. Insulin effect on tonic currents decreased the firing rate and neuronal excitability in layer 5-6 PFC cells. These effects of insulin were dependent on the activation of the PI3K enzyme, a key mediator of the insulin response within the brain. Taken together, these results suggest that insulin modulation of the GABAA-mediated tonic currents can modify the activity of neural circuits within the PFC. These actions could help to explain the alterations of cognitive processes associated with changes in insulin signaling.